(untitled) (Proceedings of International Educators Conference, 2023)
In our article, culture in foreign language teaching and study is considered and analyzed from an academic point of view. The concept of culture and its integration into language learning and teaching is controversial. Even within the same field of foreign language teaching, culture about language teaching has been approached from a range of perspectives. Cultural knowledge has a major impact on students’ language use and sometimes directly affects the outcome of communicating with native speakers.